RELASI ANTARA FIQH DAN SAINS DI ERA MODERN: SEBUAH REFLEKSI EPISTEMOLOGIS - Adib, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2014)
Ibrahim Moosa in an article (2003) has stated that relationsbetween islamic law and science in classical era arguably quite strongand harmonious. But in the modern era, relations between both ofthem is getting away and no longer eviden). However, its seems thatMoosa assessment have to be reviewed. Because, in this modern erarelations between islamic law and science showing its integrated andinterconnectivited. Development of the modern astronomy, for example,showing a very strong epistemic coherence between islamic law andscience, because it runs in tandem with the development of science andtechnology that is so rapid and fast. This paper present to photographand mapping the relations between islamic law and science in moderntimes coherenly, though probably not be called complete. Mapping relationbetween islamic law and science will be based on regular epistemologicalislamic law toward science itself.